Differences in nerve excitability properties across upper limb sensory and motor axons. (April 2022) - Carroll, Antonia S.; Howells, James; Lin, Cindy S.Y.; Park, Susanna B.; Simon, Neil; Reilly, Mary M.; Vucic, Steve; Kiernan, Matthew C.
Highlights: Ulnar and median motor axon excitability is similar; minor differences suggest increases in juxtaparanodal fast K + conductance. Modelling suggests that differences in superficial radial and median sensory excitability could reflect a tighter paranodal seal. Ulnar motor and sensory axons excitability should be used to study disease when there is a median neuropathy at the wrist. Abstract: Objective: The excitability of motor and sensory axons of the main upper limb nerves were compared to characterise the differences between nerves and provide a guide for future studies in human diseases with median neuropathy at the wrist. Methods: Axonal excitability studies were undertaken on median and ulnar motor (APB and ADM) and sensory axons (D2 and D5) and the superficial radial axons (D1) using a threshold tracking technique. Results: Compared to the median, ulnar motor axons had reduced early depolarising threshold electrotonus (TEd40(10–20 ms) p  = 0.02) and superexcitability ( p  = 0.03). The ulnar sensory axons required a stronger stimulus ( p  = 0.02) and had a larger rheobase ( p  = 0.02) than median axons, but were otherwise comparable. The superficial radial axons were "fanned-in" compared to median, and to a lesser degree ulnar axons, with greater resting I/V slope. Mathematical modelling of the radial and median sensory axons suggested that a 15.1% reduction in conductances between nodal and internodal compartments accounted for 82% of this discrepancy. Conclusions: The excitability parameters of motor and sensory axons are most comparable between median and ulnar nerves. Significance: The present study demonstrates the feasibility of, and provides normative data for, axonal excitability recordings of the radial and ulnar nerves. We suggest the use of ulnar recordings as an alternative to the median nerve in the setting of compressive neuropathy at the wrist.